The Anxiety of Parent to the Prolong Computer Games Interaction: A Survey - N. S., Razak; Rahmah, Mokhtar (Springer, Singapore, 2021)
A video or computer game has been attracting a large number of children and young people to play games repeatedly. It has become popular since this software can be installed on personal computers and mobile devices. Even though video or computer games are friendly, but the effect is adverse consequences, especially among children. This paper aims to study the consequences of video or computer games on eye health among children. This paper review the anxious of parent to their children eye health impacts due to the prolonged usage of computer games. There are 232 survey and the respondents among the parents. As a result, this study demonstrates that 76.7% of respondents among the parent show anxiety regarding eye health. These parents also concern about their children’s eye health due to the prolong computer games interaction. This survey focused on the Human-Computer Interaction (HCI) field, where the anxiety of parents to prolong usage of computer games among the children. Based on the results, the framework of the game development, which includes eye health factors, will contribute in the future.